Menilai Kinerja Laporan Keuangan Desa dengan Analisis Rasio Keuangan (Studi Literatur) - Hariany Idris (Bata Ilyas Journal of Accounting, 2022)
Â This paper aims to explore techniques for measuring village government financial performance. One of the most commonly used is the analysis using financial ratios. These financial ratios use financial statement data to then fill in the slots in the predetermined formulas. The ratio analysis includes, among others, Liquidity Ratio, Solvency Ratio, Profitability Ratio, and Activity Ratio. Analysis of the village government's financial performance is used to compare the results of one period with the previous period to find out how the financial management is. The analysis of the village government's financial performance is the most important part of its financial management in assessing the government's performance to manage village finances.Tulisan ini bertujuan untuk mengeksplorasi teknik-teknik pengukuran kinerja keuangan pemerintah desa. Salah satu yang paling umum digunakan adalah analisis menggunakan rasio keuangan. Rasio keuangan tersebut menggunakan data laporan keuangan untuk selanjutnya mengisi slot pada rumus-rumus yang telah ditentukan. Analisis rasio tersebut antara lain, Rasio Likuiditas, Rasio Solvabilitas, Rasio Profitabilitas, dan Rasio Aktivitas. Analisis kinerja keuangan pemerintah desa digunakan untuk membandingkan hasil dari satu periode dengan periode sebelumnya untuk mengetahui bagaimana pengelolaan keuangannya. Analisis kinerja keuangan Pemerintah Desa merupakan bagian terpenting untuk pengelolaan keuangannya dalam menilai kinerja pemerintahan untuk mengelolah keuangan Desa.Keywords:Financial Performance Ratio; Financial Statements; Village GovernmentÂ